PENGARUH KOMITE AUDIT, KEPEMILIKAN MANAJERIAL, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN DENGAN KULITAS AUDIT SEBAGAI VARIABLE MODERASI (STUDI EMPIRIS PADA PERUSAHAAN NON-CYCLICALS DAN CYCLICALS DI BEI PERIODE 2018-2022) - Ananda Syafana; Aina Zahra Parinduri (STMIK Widuri Jakarta, 2024)
The purpose of this research is to test and share empirical facts regarding the influence of audit committees on theintegrity of financial statements, industrial aspects of management ownership, leverage and audit quality. The purposeof this research is to determine the influence of audit committees, management ownership, industry size and financialreporting integrity with audit quality as a moderating variable The expected results of this research can be summarizedas follows: audit committees have a significant positive influence on the integrity of financial reports; corporateresponsibility has a significant positive effect on the integrity of financial reports, industrial aspects do not have amaterial impact on the completeness of financial reports. Leverage has no significant effect on the integrity of financialreports; Audit quality does not moderate the influence of the audit committee on the integrity of financial reports; Auditquality moderates the influence of corporate responsibility on the integrity of financial reports, audit quality does notmoderate the influence of industry aspects of the completeness of financial reports, audit quality does not moderate theinfluence of leverage on the completeness of financial reports.